PEMBELAJARAN MENULIS TEKS CERITA PENDEK DENGAN MENGGUNAKAN METODE FISHBOWL PADA SISWA SMA - Anggun Shinta Dewi; Siti Patimah; Aditya Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This study discusses the learning of short story text writing using fishbowl method. The aim of this research is to know fishbowl method better than Discovery Learning method which is usually used by teacher in high school student. This research was conducted in high school student. The method used is Quasi Eksperimental Design which is the development of True Experimental Design. The Quasi Experimental Forms used are the Pretes-Posttes Control Group Design. The sample used in this research is the students of class A and B high school , each of which is 23 people. Based on the results of the research can be concluded Fishbowl method is better than the Discovery Learning method on the high school student , at the time the students after being treated (treatment) using fishbowl method of acquisition value obtained by students the result is very good, can seen from the resultsof the final test (posttest) gets an average score of 64.5, while students after being treated (treatment) using the Discovery Learning method the value obtainedby students either, can be seen fromthe results of the end test (posttest) 58.